PREVALENSI DAN KARAKTERISTIK PENDERITA HIPERTENSI PADA PENDUDUK DESA BANDA BARU KABUPATEN MALUKU TENGAH TAHUN 2020 - Joshua Jonatan Gonidjaya; Bertha J. Que; Nathalie E. Kailola; Elpira Asmin; Christiana R Titaley; Indrawanti Kusadhiani (Fakultas Kedokteran Universitas Pattimura, 2021)
Introduction. Hypertension accounts about 1,13 billion cases in the world. Because it rarely gives off symptoms, hypertension conditions are generally not recognized, so that other morbidity that can occur are congestive heart failure, left ventricle hypertrophy, stroke, end stage renal failure, or even death. Aim. This research aims to determine prevalence of hypertension in Banda Baru Village, Central Maluku District in 2020. Methods. This research uses a descriptive study with cross sectional approach by doing interview, questionnaire and research variable measurement. Results. Among 168 respondence, number of cases with hypertension are 52 respondence (31%) and 116 respondence (69%) are not hypertension. The age group suffered most is 34-45 years old as much 17 cases (38,6%), but the age group suffered most according to percentage is 56-65 years old as much 63,2%. Respondence with hypertension most suffered by female as much 36 cases (36,4%). Hypertension prevalence based on family history as much 28 cases (37,8%). Hypertension prevalence based on alcohol consumption behavior as much 4 cases (12,5%). Hypertension prevalence based on smoking behavior as much 14 cases (24,1%). Hypertension prevalence based on nutrition status with BMI ≥25 as much 29 cases (53,7%). Conclusion. Cases of hypertension are common in older age, female, respondence with hypertension in family history, and obesity.